Harnessing spectrophotometry resolution power for determining ternary mixture for respiratory disorders treatment in their pharmaceutical formulation - AlSalem, Huda Salem; Algethami, Faisal K.; Magdy, Maimana A.; Ali, Nourudin W.; Zaazaa, Hala E.; Abdelkawy, Mohamed; Gamal, Mohammed; Abdelrahman, Maha M. (PLOS ONE, 2024)
A ternary mixture incorporating Hydroxyzine hydrochloride (HYX), Ephedrine hydrochloride (EPH) and Theophylline (THP) frequently prescribed for the treatment of respiratory diseases. Herein, two spectrophotometric methods are designated and applied to resolve these three components in their mixture. Method A is ratio-subtraction combined with derivative spectrophotometry, where THP can be determined directly at its λmax 271 nm (neither HYX or EPH interfere), then for determination of HYX and EPH, the ternary mixture was divided by 22 μg/mL of THP and after subtraction of the plateau region, HYX can be determined directly at its λmax 234.2 nm (absence of EPH intervention). Finally, the third derivative (3D) spectrophotometric approach was utilized to estimate EPH by detecting the peak amplitude at 222 nm with Δλ = 4 and a scaling factor 100. Principal Component Regression (PCR) and Partial Least Squares (PLS), two multivariate calibration approaches, were applied effectively in Method B. This method effectively quantified the mixture under investigation by using the absorption spectra obtained from suitable solutions of the three components in the 210–230 nm region. The calibration models were evaluated using cross-validation with PCR and PLS, producing statistical characteristics that demonstrate the effectiveness of the calibration models. Synthetic and pharmaceutical preparations were also used to conduct external validation. In pharmaceutical formulation, these methods were successfully applied to analyze HYX, EPH, and THP without overlap from formulation’s excipients. Moreover, the study’s findings were statistically contrasted with those of earlier reported HPLC method. Appraisal approaches were used to determine whether the new spectrophotometric methods had an adverse environmental impact involving the Green Analytical Procedure Index (GAPI) and the AGREE (Analytical Greenness). These evaluations delivered information about the methods’ eco-friendliness and sustainability, proving that they are in line with ecologically attributed practices. Furthermore, the Blue Applicability Grade Index (BAGI) was utilized to identify and verify the feasibility and practicality of the suggested approaches.